An Aqueous Extract of Black Rice Bran from the Cibeusi Variety Prevents Anemia and Hypertriglyceridemia in Rats - Nurlaili, Enny Purwati; Astuti, Mary; Marsono, Yustinus; Naruki, Sri (Pakistan Journal of Nutrition, 2016)
Rice is a leading staple food in Southeast Asia and it is typically milled before consumption. Black rice found in Indonesia is classified as Oryza sativa L. The color in the grain is caused by anthocyanin pigments that give the hulled rice a dark purple color. We found that extracts from black rice bran have high levels of iron and anthocyanins. The objective of this study was to evaluate the potential of an aqueous extract of black rice bran to prevent anemia and hypertriglyceridemia in vivo. Anemia and hypertriglyceridemia were induced in twenty-eight three-week old male albino Wistar rats (Rattus norvegicus); the rats were divided into a control (C) group or 3 treatment groups of bran (B), bran extract (E), or extraction residue (R). The results showed that differences among the groups based on feed consumption, Hemoglobin Regeneration Efficiency (HRE) and the erythrocyte morphology of rats were not significant. Black rice bran aqueous extract prevented anemia and hypertriglyceridemia by increasing the hemoglobin Hb level from 7.21 to 12.96 g/dl and by reducing triglycerides from 179.29 to 56.55 mg/dl.